Synthesis and bioevaluation of 2-phenyl-5-methyl-2H-1, 2, 3-triazole-4-carboxylic acid/carbohydrazide derivatives as potent xanthine oxidase inhibitors. Issue 115 (12th December 2016) - Shi, Ailong; Wang, Defa; Wang, He; Wu, Yue; Tian, Haiqiu; Guan, Qi; Bao, Kai; Zhang, Weige
Abstract : A series of 2-phenyl-5-methyl-2 H -1, 2, 3-triazole-4-carboxylic acids/carbohydrazides as analogues of febuxostat were synthesized and evaluated for their in vitro xanthine oxidase (XO) inhibitory activity. Abstract : A series of 2-phenyl-5-methyl-2 H -1, 2, 3-triazole-4-carboxylic acids/carbohydrazides as analogues of febuxostat were synthesized and evaluated for their in vitro xanthine oxidase (XO) inhibitory activity. Among these compounds, the carboxylic acid derivatives7a–h and8a–h exhibited high potency in the submicromolar/nanomolar range. Steady-state kinetics experiment revealed that7f was a mixed-type inhibitor of xanthine oxidase. In addition, a molecular docking study of7f was performed to determine its binding mode at the active site of xanthine oxidase.